Patient-controlled epidural analgesia for labor – a step forward in Ukrainian obstetrics - Grizhimalsky, Yevhenii; Harha, Andrii (Pain medicine, 2019)
Labour pain is recognized by some women as the most severe pain that they have ever felt in their life. Epidural analgesia is an effective method of pain relief in labour and is considered as the gold standard of analgesia for delivery. Traditionally, epidural analgesia in Ukraine is performed without the ability for the patient to control the process of anesthesia. The authors became interested in the delivery of local anesthetics by patientcontrolled epidural analgesia instead of the traditional physician methods. In randomized controlled studies there is an evidence that the PCEA method tends to improve the quality of pain relief and increase the patient satisfaction.